2010
DOI: 10.1099/ijs.0.013276-0
|View full text |Cite
|
Sign up to set email alerts
|

Actinokineospora baliensis sp. nov., Actinokineospora cibodasensis sp. nov. and Actinokineospora cianjurensis sp. nov., isolated from soil and plant litter

Abstract: Six actinomycete strains isolated from soil and plant-litter samples in Indonesia were studied for their taxonomic position by using a polyphasic approach. Phylogenetically, all the strains were located in the broad cluster of the genus Actinokineospora. Chemotaxonomic data [cell-wall diamino acid, meso-diaminopimelic acid; cell-wall peptidoglycan, type III (A1γ); major sugars, galactose and arabinose; major menaquinone, MK-9(H4); major fatty acid, iso-C16 : 0; major phospholipid, phosphatidylethanolamine] sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Molecular identification of the ID04-0555 strain was conducted based on the 16S rRNA gene as established by Lisdiyanti et al (2010). The 16S rRNA gene was amplified via polymerase chain reaction (PCR) technique using a pair of 9F and 1510R primers (Additional file 1: Table S1) (Burggraf et al 1992).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular identification of the ID04-0555 strain was conducted based on the 16S rRNA gene as established by Lisdiyanti et al (2010). The 16S rRNA gene was amplified via polymerase chain reaction (PCR) technique using a pair of 9F and 1510R primers (Additional file 1: Table S1) (Burggraf et al 1992).…”
Section: Methodsmentioning
confidence: 99%
“…Fortunately, Indonesia is also rich in terrestrial microbes, particularly in actinomycetes. Several scientists have reported that actinomycetes isolated from Indonesian soils and leaf-litters represent new species and demonstrate genus diversity (for example, Otoguro et al 2009, 2011; Lisdiyanti et al 2010; Yamamura et al 2010). Extensive exploration of industrially useful enzymes has been conducted from these actinomycetes, such as inulin fructotransferase (Pudjiraharti et al 2011, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Actinokineospora belongs to the family Actinosynnemataceae under the phylum Actinobacteria (2). Members of Actinokineospora are widespread in terrestrial environments, including soil and plants (3, 4), and were recently isolated from marine sponges (1). So far only two draft genomes of the genus Actinokineospora are available (BioProject identification [ID] 188797 and 174972 [http://www.ncbi.nlm.nih.gov/]).…”
Section: Genome Announcementmentioning
confidence: 99%
“…Currently, this genus, which belongs to the family of Pseudonocardiaceae, contains thirteen species with validly published names: Actinokineospora riparia (Hasegawa 1988), Actinokineospora inagensis, Actinokineospora globicatena, Actinokineospora terrae, Actinokineospora diospyrosa (Tamura et al 1995), Actinokineospora auranticolor, Actinokineospora enzanensis (Otoguro et al 2001), Actinokineospora fastidiosa (Labeda et al 2010), Actinokineospora baliensis, Actinokineospora cibodasensis, Actinokineospora cianjurensis (Lisdiyanti et al 2010), Actinokineospora soli (Tang et al 2012) and Actinokineospora bangkokensis (Intra et al 2013).…”
Section: Introductionmentioning
confidence: 99%